Pathogenesis, prevention, and management of bleeding and thrombosis in patients with liver diseases - Lisman, Ton (Res Pract Thromb Haemost, 2017)
ESSENTIALS: Patients with liver diseases may acquire substantial changes in all components of hemostasis. Hemostasis is in unstable balance due to simultaneous changes in pro‐ and antihemostatic systems. Intrahepatic activation of hemostasis may contribute to disease progression. Optimal strategies for prevention and treatment of bleeding and thrombosis are currently unknown. Patients with liver diseases may develop alterations in all components of the hemostatic system. Thrombocytopenia, low levels of coagulation factors and inhibitors, low levels of fibrinolytic proteins, and increased levels of endothelial‐derived proteins such as von Willebrand factor are all part of the coagulopathy of liver disease. Due to concomitant changes in pro‐ and antihemostatic drivers, the net effects of these complex hemostatic changes have long been unclear. According to current concepts, the hemostatic system of patients with liver disease is in an unstable balance, which explains the occurrence of both bleeding and thrombotic complications. This review will discuss etiology and management of bleeding and thrombosis in liver disease and will outline unsolved clinical questions. In addition, we will discuss the role of intrahepatic activation of coagulation for progression of liver disease, a novel paradigm with potential consequences for the general management of patients with liver disease.